PENINGKATAN KETERAMPILAN AKUNTANSI SISWA/I SMK KRISTEN RAHMANI MELALUI PELATIHAN SOFTWARE ACCURATE - Wirianata, Henny; Metio Alberto; Rusi (Jurnal Serina Abdimas, 2024)
In this Community Service Activity, Untar Team provided training on using Accurate accounting software to students at SMK Kristen Rahmani. This training aims to increase students' competence in mastering information technology in the field of accounting. Due to time constraints and the available number of modules, this training only focuses on the Purchasing Cycle. This training held offline on Thursday, September 12 2024. The software used is Accurate ver. 5 for Education. The implementation method used is the conventional method with lectures providing presentation of material, discussions and practice questions. In this training, Untar Team explained recording in Accurate related to the purchasing process from suppliers. The practice questions consists of forms used to record purchase transactions from suppliers. During the training, the students who participated looked enthusiastic because this training used an interactive learning method, which participants were asked to practice directly using the Accurate software. Participants seemed capable and understood the activity to enter purchase data transactions in Accurate. After attending this training, they gain understanding and knowledge about how to record in the Accurate software related to requests for purchasing goods, ordering goods from suppliers, receiving goods from suppliers, receiving and paying bills to suppliers, as well as returning goods that do not match the order. Thus, this training has increased the competency of training participants in using Accurate accounting software. ABSTRAK Pada kegiatan PKM kali ini, Tim PKM Untar memberikan pelatihan tentang penggunaan software akuntansi Accurate kepada siswa/i SMK Kristen Rahmani. Pelatihan ini bertujuan untuk meningkatkan kompetensi siswa-siswi dalam menguasai teknologi informasi di bidang akuntansi. Karena keterbatasan waktu dan banyaknya modul yang ada, pelatihan kali ini hanya fokus pada Siklus Pembelian. Pelatihan ini dilaksanakan pada hari Kamis, 12 September 2024, secara offline/luring. Software Accurate yang digunakan adalah versi 5 untuk Education. Metode pelaksanaan yang digunakan adalah cara konvensional dengan ceramah memberikan pemaparan materi, diskusi, dan latihan soal. Dalam pelatihan ini, Tim PKM Untar membahas pencatatan dalam software Accurate yang berkaitan dengan proses pembelian dari pemasok. Latihan soal berupa input form-form yang digunakan untuk mencatat transaksi pembelian dari pemasok. Selama pelatihan, siswa/i peserta pelatihan terlihat antusias karena pelatihan ini menggunakan metode pembelajaran yang interaktif yaitu peserta diminta mempraktekkan langsung latihan soal menggunakan software Accurate. Peserta terlihat mampu dan memahami kegiatan peng-input-an transaksi pembelian dalam Accurate. Setelah mengikuti pelatihan ini, mereka mendapatkan pemahaman dan pengetahuan tentang cara mencatat dalam software Accurate yang berkaitan dengan permintaan pembelian barang, pemesanan barang kepada pemasok, penerimaan barang dari pemasok, penerimaan dan pembayaran tagihan kepada pemasok, serta pengembalian barang yang tidak sesuai pesanan. Dengan demikian, pelatihan ini telah meningkatkan kompetensi peserta pelatihan dalam menggunakan software akuntansi Accurate.